An experimental study on the skin irritant potential of Dinh Tho patch - Tu Anh, Dam Thi; Van Anh, Pham Thi; Phuong, Do Thi Minh; Hanh, Hoang My; Trung, Le Hai; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2025)
Dinh Tho patches are the transdermal combination of medicinal herbs including Dracaena cambodiana Pierre ex Gagnep, Cinnamomum cassia, Kaempferia galanga, Homalomena occulta, Caesalpinia sappan, Illicium verum, Artemisia vulgaris and Reynoutria japonica with the intended indication to treat symptoms of swelling, bruising, tension and pain of the musculoskeletal system. This study was carried out to examine the skin irritation of Dinh Tho patches in experimental animals. Each individual rabbit was applied (2.5x2.5cm) Dinh Tho patch on one side of the dorsal area and (2.5x2.5cm) sodium chloride-impregnated gauze in the other size as control. The degree of erythema and edema formation were observed and scored at 1 hour, 24 hours, 48 hours and 72 hours after patch removal. Our results showed that grade 1 or grade 2 erythema only appeared 1 hour after removal of the test product. There were no signof erythema, edema or other skin injury observed after 24 hours, 48 hours or 72 hours. It can be concluded that Dinh Tho patch did not cause skin irritation in rabbits.